2017
DOI: 10.1137/16m107222x
|View full text |Cite
|
Sign up to set email alerts
|

Bloch Waves in an Arbitrary Two-Dimensional Lattice of Subwavelength Dirichlet Scatterers

Abstract: We study waves governed by the planar Helmholtz equation, propagating in an infinite lattice of subwavelength Dirichlet scatterers, the periodicity being comparable to the wavelength. Applying the method of matched asymptotic expansions, the scatterers are effectively replaced by asymptotic point constraints. The resulting coarse-grained Bloch-wave dispersion problem is solved by a generalised Fourier series, whose singular asymptotics in the vicinities of scatterers yield the dispersion relation governing mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 54 publications
1
20
0
Order By: Relevance
“…ε . Taking into account ( 5), ( 7), ( 8), and when j = k, using the integration by parts one can represent the boundary integrals in (12) via the integrals over F (j) ε , and hence the representation (12) takes the form…”
Section: The Algebraic Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…ε . Taking into account ( 5), ( 7), ( 8), and when j = k, using the integration by parts one can represent the boundary integrals in (12) via the integrals over F (j) ε , and hence the representation (12) takes the form…”
Section: The Algebraic Systemmentioning
confidence: 99%
“…Analysis of waves in a plane with semi-infinite arrays of isotropic scatterers is discussed in [11]. Waves governed by the Helmholtz equation in a doubly periodic array with an elementary cell containing several scatterers were analysed in [12], based on the approach of [10], [11] and asymptotics representing singular perturbation leading-order approximations, similar to simplified cases of [2], [6] and [7]. Dispersion of waves analysed in [12] shows dynamic anisotropy linked to the scatterers within the elementary cell.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, it can be shown that (3.4) still holds at intermediate radial distances from the centerline, i.e., b r a, if only the cross-sectional radius bf (φ) is replaced by the so-called 'conformal radius', say bf * (φ), of the cross-sectional geometry at the azimuthal angle φ. Working in the corresponding crosssectional plane, the conformal radius bf * (φ) can be extracted from a conformal mapping from the exterior of a circle of that radius to the domain exterior to the true cross section (see, e.g., [33,Chapter 5] and [59]). In particular, for elliptical cross sections with semi-diameters bσ 1 (φ) and bσ 2 (φ), one finds bf * (φ) = (bσ 1 + bσ 2 (φ))/2.…”
Section: Further Geometric Extensions a Arbitrary Cross-sectional Shapesmentioning
confidence: 99%
“…Equations (2) and (4) are, for metallic scatterers and with r constant, the Helmholtz equation and we can draw upon efficient, rapid, semi-analytical methods created for small inclusions as described in [58]. These are derived in [25] (based upon an extension of [69]) utilizing matched asymptotic expansions, each circular scatterer -of radius ηa -is approximated by a monopole and dipole source term whose coefficients, a mono and b di are a priori unknown constants. These unknown constants can trivially absorb factors of a or r , the analysis from [25] remains largely unchanged, that is for a single scatterer…”
Section: A Planar Array Of Small Circular Scatterersmentioning
confidence: 99%